The labor market effects of disability benefit loss - Anikó Bíró; Cecília Hornok; Judit Krekó; Daniel Prinz; Ágota Scharle (Kiel Institute for the World Economy (IfW Kiel), 2023)
Disability benefits are costly and tend to reduce labor supply. While spending can be contained by careful targeting, correcting past flaws in eligibility rules or assessment procedures may entail welfare costs. We study a major reform in Hungary that reassessed the health and working capacity of a large share of beneficiaries. Leveraging age and health cutoffs in the reassessment, we estimate employment responses to loss or reduction of benefits. We find that among those who left disability insurance due to the reform 58% were employed in the primary labor market, 6% participated in public works and 36% were out of work without benefits in the post-reform period. The consequences of leaving disability insurance sharply differed by pre-reform employment status. 81% of beneficiaries who had some employment in the pre-reform year worked, while only 33% of those without pre-reform employment did. The gains of the reform in activating beneficiaries were small and strongly driven by pre-reform employment status. This points to the importance of combining financial incentives with broader labor market programs that increase employability.
Keywords: H55; J14; 330; disability insurance; benefit reduction; employment